Post-Merger Employee Satisfaction in Nepal’s Commercial Banks: Key Determinants and Strategic Implications - Kandel, Madan; Thapa, Krishna Bahadur; Shrestha, Shanti (International Journal of Atharva, 2025)
This study examines the effects of mergers and acquisitions (M&A) on employee job satisfaction within Nepal's commercial banking industry, emphasizing the significance of post-merger integration (PMI), communication efficacy, and job security. Data were collected from 112 workers of Prabhu Bank and Nabil Bank utilizing a descriptive and explanatory research approach through structured questionnaires. The results indicate that PMI (Beta = 0.381) is the most significant predictor of employee happiness, succeeded by job security (Beta = 0.255) and communication efficacy (Beta = 0.205). The research underscores the significance of seamless integration, clear communication, and guarantees of job security in improving employee morale and commitment during mergers. These findings correspond with the current literature while tackling the distinct issues of Nepal's banking system, where mergers frequently result in restructuring and alterations in roles. The report concludes with actionable advice for organizational leaders to emphasize human resource considerations during mergers, so assuring sustained success and employee happiness.